ON DIFFERENTIATION BETWEEN METAPHORICAL AND MENTAL IMAGES VERBALIZED IN EMOTIVE PROSE (ON THE TEXTS OF SMALL EMOTIVE PROSE BY E. I. ZAMYATIN) - E. Astashina (Гуманитарные и юридические исследования)
Nowadays achievements in metaphor studies let us say that the statement that the nature of metaphor is mental and figurative is axiomatic. Trying to fix the ideal, metaphor like any mental image may be denoted by means of the natural language instruments. The mediate demonstration of the ideal nature makes metaphor verbalization and the one of the mental image nondescript that is aggravated by their core similarity and absence of special figures of expressing mental images taking into consideration their crucial omni-fariosity to be verbalized. The author of the article has faced the taxonomic problem of characterization of certain emotive prose texts by E. I. Zamyatin according to the type of imagery. This proves the relevance of the scientific solution of the problem to distinguish the intensional and extension-al of concepts metaphorical image and psychic image. The literal material of Zamyatin emotive prose discourse analyzed in this article shows practical difficulty of interpreting mental images in accordance with their nature. There has been constructed a parametric succession of constituents of notions of metaphorical and mental images with the help of the methods of contextual analysis of the natural language text, of self-observation as the empiric analysis of the language material, of theoretical synthesis of speech experience with further schematization. The succession was applied to the analysis of texts by E. I. Zamyatin. The obtained theoretical tool of linguistic analysis of non-elementary language code, tested in private practice, is the scientiic novelty of this work. The data of the work may be used for the interpretation and analysis of any emotive prose piece of work and analysis of any emotive prose text as mental images are intentionally verbalized as an expressive means as often as metaphorical ones. This study complements the theoretical knowledge of metaphorology, stylistics, linguistic analysis of the text, language theory, as well as applied knowledge of these scientiic branches as scientiic disciplines of educational programs of secondary and higher schools.